2014
DOI: 10.21608/jpp.2014.53631
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sowing Dates and Seed Treatments on Productivity and Seed Quality of Some Wheat Cultivars

Abstract: A field trial and a laboratory experiment were conducted during 2011/2012 and 2012/2013 seasons. The main objective of this research was to study the performance of some wheat cultivars as affected by sowing dates and seed treatments and their effect on growth, yields and its components and seed quality. Each sowing date (10 th November, 25 th November and 10 th December) was practiced in separate experiments. Every experiment was carried out in split-plot design with four replications. The main plots were occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…The yield attributing factors such as number of grains per spike and thousand grain weight were higher whereas, sterility percentage was lower in early sown wheat thus contributing higher seed yield of wheat on early sowing than late sown wheat. Similar results were also observed by Badawi et al (2014) who reported higher seed yield on earlier than late sown wheat.…”
Section: Discussionsupporting
confidence: 89%
“…The yield attributing factors such as number of grains per spike and thousand grain weight were higher whereas, sterility percentage was lower in early sown wheat thus contributing higher seed yield of wheat on early sowing than late sown wheat. Similar results were also observed by Badawi et al (2014) who reported higher seed yield on earlier than late sown wheat.…”
Section: Discussionsupporting
confidence: 89%
“…While delaying the sowing date until January 5 (a late sowing date) reduced electrical conductivity values, which is good for seed quality, it also produced the highest protein content and wet and dry gluten percentage values. According to (Abdullah et al, 2007;Motzo et al,2007;Yan et al,2008;Badawi et al, 2014;Eslami et al,2014;Yusuf et al,2019), the effect of planting date on grain quality. The favorable effect of sowing wheat on December 5 may be attributed to the seasonable environmental conditions during this period, such as temperature, relative humidity, day length, and light intensity, which allow for rapid and high germination and increase yield components as well as grain yield per unit area (Seleiman et al 2011;Gul et al, 2012;Kaur, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It is also seen as a non-monetary input. Thus, choosing a genotype with high acclimation and seeding wheat at the right time based on local environmental conditions are the best ways to maximize yields and grain quality characteristics (Badawi et al, 2014). Productivity will grow under any suitable circumstance that lengthens the vegetative and reproductive stages (Egliet et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation